“It all started with the match factory in Debrecen”: Swabians from the Tokaj-Hegyalja area as forced laborers in the former Soviet Union - Endrész, Árpádné; Scholtz, Róbert Gergely (Ethnographica et Folkloristica Carpathica, 2020)
In the last year of World War II, the Soviet army occupied Eastern Hungary. Following the military order of Marshal Malinovsky, the ethnic Germans in Hungary were forced to perform forced labor. The abducted people were branded war criminals and taken to coal mines in the Don-bassin, the so called "soviet paradise". Altogether 348 people were taken from the ethnic german settlements of Tokaj-Hegyalja, 30 of whom never returned. The youngest of the civilians was 16 years old and the oldest 65. They were told that they had to go to the match factory in Debrecen for a "little work / Malenkij robot". Most of the deportees could only return home after 2-4 years - spent in inhumane contitions. Our project commemorates their memories. Since the years of silence are over, nowadays, we are free to talk about events that have taken place 70 years ago. We hope they will never happen again.